KEDUDUKAN PEREMPUAN DALAM PEMBAGIAN HARTA WARIS MENURUT MASYARAKAT KHONGHUCU PALEMBANG - Yulia Puspita (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2020)
The position of women in the traditions of the previous Confucian society was less favorable, because women did not have the right to organize their own live. There was always a male role who controls all aspects of life. The same goes for the distribution of inheritance. Boys were prioritized over girls, because the concept of customary law and boys are responsible for the survival of the extended family. While the daughter when married she becomes part of her husband’s extended family. However, there are some confucian traditions that have adapted to modern times, such as the Confucian community at Jl. Puding Kel. Demang Lebar Daun Kec. Ilir Barat I Palembang. Most of people in the community, the distributian of inheritance is divided equally between men and women. This type of research is field research. The type of data used is qualitative data.